(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial Intelligence (AI) is transforming the education sector at a radical pace by providing personalized instruction and by providing simulations to enhance the visualization skills of learners so that teaching-learning process become a fruitful experience. AI in education encompasses Intelligent Tutoring Systems (ITS), AI-based tests and administrative automation. India has started integrating AI into education policies through the efforts of the All-India Council for Technical Education (AICTE) and the National Education Policy (National Education Policy 2020 Ministry of Human Resource Development Government of India, 2020). This research paper aims to analyze AI’s impact on education; innovative practices incorporated in educational scenarios as a part of AI-Integration across various disciplines and to design a conceptual framework based on the adaptability and innovation of Artificial Intelligence in educational contexts.